Anxiety and 10-Year Risk of Incident Dementia—An Association Shaped by Depressive Symptoms: Results of the Prospective Three-City Study - Mortamais, Marion; Abdennour, Meriem; Bergua, Valérie; Tzourio, Christophe; Berr, Claudine; Gabelle, Audrey; Akbaraly, Tasnime N. (Frontiers in Neuroscience, 2018)
Background Anxiety is common in patients with cognitive impairment and dementia. However, whether anxiety is a risk factor for dementia is still not known. We aimed to examine the association between trait anxiety at baseline and the 10-year risk of incident dementia to determine to which extent depressive symptoms influence this relationship in the general population. Methods Data came from 5234 community-dwelling participants from the Three-City prospective cohort study, aged 65 years at baseline and followed over 10 years. At baseline, anxiety trait was assessed using the Spielberger State-Trait Anxiety Inventory (STAI), and depressive symptoms using Center for Epidemiologic Studies-Depression Scale (CESD). Use of anxiolytic drugs was also considered. Diagnoses of dementia were made at baseline and every 2 years. To examine the relationship between anxiety exposures and risk of incident dementia, Cox proportional hazard regression models were performed. Results Taking anxiolytic drugs or having high trait anxiety (STAI score≥44) increased the risk of dementia assessed over 10 years of follow-up (Hazard Ratio (HR)=1.39, 95%CI: 1.08 to 1.80], p=0.01 and HR=1.26, 95%CI: 1.01 to 1.57], p=0.04, respectively), independently of a large panel of socio-demographic variables, health behaviours, cardio-metabolic disorders and additional age-related disorders such as cardiovascular diseases, activity limitations and cognitive deficit. However, the associations were substantially attenuated after further adjustment for depressive symptoms. Conclusion Our findings suggest that depressive symptoms shape the association between anxiety trait and dementia. Further research is needed to replicate our findings and extrapolate our results to anxiety disorders.